DEVELOPMENT OF POLYCLONAL ANTIBODIES (IGY-ANTI NS3 AND SPIKE) CONJUGATED WITH CURCUMIN CARBON DOTS FOR SARS-COV-2 ANTIGEN DETECTION BASED ON FLUORESCENCE IMMUNOSENSOR - Kezia Soetomo, Meilisa
Carbon nanodots are a type of nanoparticle with carbon as the main material that has good biocompatibility and fluorescence properties so that it can be used in biological field applications such as diagnostic kits. Antibodies can be conjugated with nanoparticles as fluorescence agents used to detect antigens in diagnostic kits. Commercialized nanoparticle-conjugated antibodies for antigen detection currently have a high cost with very little volume. Therefore, it is important to find other alternatives that can reduce production costs to replace commercial nanoparticle-conjugated antibodies. In this study, polyclonal antibodies from chicken eggs conjugated with curcumin carbon nanodots were developed that can replace nanoparticle-conjugated antibodies for antigen detection. Polyclonal antibodies were conjugated with curcumin carbon nanodots using EDC/NHS coupling method. The concentration of antibody used was 0.005 mg/ml and the concentration of curcumin carbon nanodots used was 1.5; 1; 0.5 mg/mL. Confirmation of the success of the conjugation was done by comparing the fluorescence results of antibody conjugated curcumin carbon nanodots with curcumin carbon nanodots without antibody as a control. Then Antibody conjugated curcumin carbon nanodots were added with graphene oxide (GO). GO concentration was optimized with variations of 0, 25, 50, 75, and 100 ?g/mL. The GO incubation time was optimized periodically by looking at the GO fluorescence value every 5 minutes for 60 minutes. Afterwards, multi-epitope antigens were tested against GO with curcumin carbon nanodots-conjugated antibodies. Confirmation of the success of curcumin carbon nanodots-conjugated antibodies in detecting antigens was done by comparing the fluorescence value between curcumin carbon nanodots-conjugated antibodies without GO as a positive control with curcumin carbon nanodots-conjugated antibodies added graphene oxide as a negative control. The results showed that the antibody was successfully conjugated with curcumin carbon nanodots. This is evidenced by the wavelength shift in all Ab-Cds conjugation excitations when compared to the control. The optimal GO concentration was 75 mg/ml with an incubation time of 15 minutes. Antibody conjugated curcumin carbon nanodots successfully detect antigens as indicated by the comparison of fluorescence values between treatments with positive and negative controls. This is reinforced by the results of statistical tests that show a p-value <0.05 so that there is a significant difference between the treatment and the negative control. In contrast, the statistical test results between the treatment and positive control showed a p-value> 0.05 so that there was no significant difference between the two. Based on this, it can be concluded that in this study the antibody has been successfully conjugated with curcumin carbon nanodots and can be used to detect SARS-COV-2 antigen in a fluorescence immunosensor system.